Local Islam and Javanese Culture Penetration: Muslim Alif Rebo Wage (Aboge) Negotiations in Identity Formation - Nina Mariani Noor; Ahmad Muttaqin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2022)
This article aims to explain the efforts of Aboge Muslims as a group that gains penetration from mainstream culture to negotiate their identity. Aboge (Alif Rebo Wage) is a Muslim group in Java that has a Kejawen Islamic identity. In Banyumas District, Central Java, the Aboge identity was built based on the Penginyongan culture whose position is a subculture of Javanese. Using a critical paradigm with the theoretical approach of genetic structuralism developed by Pierre Bourdieu, this article shows that Aboge identity negotiations are carried out by capitalizing on the Penginyongan culture as a locality that has a strategy in the era of regional and village autonomy. The result of this study reveals that Aboge takes the space left by the Banyumasan community because it is inferior to standard Javanese. This is because Penginyongan culture, which includes language, tradition, and religion, tends to be positioned as marginal, assumed to be deviant, and misrepresented. Standard culture uses the instrument of power that is owned to maintain its dominance through the formation of a stratified structure. This structure is used to distribute other variations at different positions with the epicenter point filled by the standard culture. In the context of language, bandek Javanese (Yogyakarta and Solo) is the standard, outside of which includes the North Coast, East Java, and Banyumasan are dialects. Locality gained momentum during the period of regional and village autonomy which demanded its development to explore and accommodate local culture. Aboge with Penginyongan identity then becomes a manifestation that represents locality.